Job satisfaction memediasi pengaruh organizational commitment terhadap job performance - Bunga Ambar Dini; Dwiarko Nugrohoseno (Universitas Negeri Surabaya, 2026)
This study aims to examine the effect of organizational commitment on job performance, with job satisfaction as a mediating variable. The research employs a quantitative approach, using data collected via questionnaires distributed to employees and analyzed using the Partial Least Squares (PLS) method. The findings reveal that organizational commitment has a significant positive effect on job performance. Moreover, organizational commitment positively affects job satisfaction, which, in turn, positively influences job performance. The results further indicate that job satisfaction mediates the relationship between organizational commitment and job performance. Employees who are committed to their organization tend to experience higher job satisfaction, which enhances their motivation and intrinsic drive to perform better. This suggests that job satisfaction acts as a psychological mechanism that strengthens the link between organizational commitment and job performance. These findings emphasize the importance of organizations implementing strategies that cultivate both commitment and employee satisfaction to sustain optimal performance. Fostering a positive work environment and aligning employee values with organizational goals can be a strategic approach to improving workforce productivity and overall organizational effectiveness.